2017
DOI: 10.3928/1081597x-20170201-01
|View full text |Cite
|
Sign up to set email alerts
|

Noncontact Quantification of Topography of Anterior Corneal Surface and Bowman's Layer With High-Speed OCT

Abstract: A noncontact method to quantify the topography and aberrations of corneal surfaces with OCT was presented. OCT measurements yielded greater curvature and aberrations than Pentacam in both normal and keratoconic eyes. [J Refract Surg. 2017;33(5):330-336.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 21 publications
0
39
0
Order By: Relevance
“…Further study is also needed to quantify the correlations between curvature and wavefront aberration indices preoperatively in normal corneas. Also, there is a need to develop newer ectasia detection scores using the E‐B interface curvature and aberrations . In summary, this study provided new insights on remodeling of the stroma after PRK.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Further study is also needed to quantify the correlations between curvature and wavefront aberration indices preoperatively in normal corneas. Also, there is a need to develop newer ectasia detection scores using the E‐B interface curvature and aberrations . In summary, this study provided new insights on remodeling of the stroma after PRK.…”
Section: Discussionmentioning
confidence: 89%
“…A recent study has shown for the first time application of the high‐speed OCT to map the curvature and aberrations of the A‐E and E‐B interfaces in keratoconic eyes . The OCT method was a significant improvement over the other technique of intraoperative assessment of E‐B interface in an eye undergoing surgery .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this respect, we were the first to show noncontact elevation derived topography imaging of the Bowman's layer in normal and KC eyes with OCT . In cases with clinical keratoconus, it clearly showed a greater severity of the disease than topography of the anterior corneal surface . However, whether Bowman's topography led to improved detection of FFKC relative to current tomography devices is unknown.…”
Section: Introductionmentioning
confidence: 95%